Clinical and measurement variables affecting halitosis intensity following cysteine challenge test - Wanki Lee; Jung Hwan Jo; Young-Seok Park; Ji Woon Park (Scientific Reports)
Abstract The cysteine challenge test is a reliable and efficient method for halitosis diagnosis and assessing treatment effectiveness by measuring the capacity to produce hydrogen sulfide. However, several aspects related to the test including evaluation timing and total duration following cysteine loading has not been investigated in-depth and a standardized protocol is yet to be established. This observational study compared concentrations of volatile sulfur compounds (VSCs) following cysteine challenge at various time points based on different measurement tools to investigate clinical factors influencing the results. Cysteine challenge (rinsing for 30 s with 5 mL of 6 mM L-cysteine solution) was applied in 100 healthy subjects. VSC concentration of oral cavity gas was analyzed with standard and portable gas chromatography (GC) at 5 time points (before, immediately, 10, 20, and 30 min after cysteine challenge). The Community Periodontal Index of Treatment Needs (CPITN), Winkel’s Tongue Coating Index, and salivary flow rate were assessed. VSC levels significantly increased immediately after cysteine challenge (p < 0.001 for hydrogen sulfide, p < 0.001 with standard GC and p < 0.05 with portable GC for methyl mercaptan). Levels significantly decreased at 10 min after cysteine challenge except for methyl mercaptan measured with standard GC (p < 0.001). Subjects still showing VSCs 20 min after cysteine challenge was less than 15% of those initially positive. The amount of tongue coating showed significant association with methyl mercaptan levels immediately after (β = 0.202, p = 0.049) and 10 min following (β = 0.207, p = 0.045) cysteine challenge and CPITN showed acceptable discriminative power for persistent detection of methyl mercaptan (cut-off = 1.5, AUC = 0.668). Cysteine challenge may enhance the possibility of detecting VSCs during halitosis diagnosis. Standardized test protocols should address measurement timing, tools used, and tongue coating levels as clinical factors influencing VSC detection.